A comprehensive epigenome atlas reveals DNA methylation regulating skeletal muscle development. Issue 3 (12th January 2021) - Yang, Yalan; Fan, Xinhao; Yan, Junyu; Chen, Muya; Zhu, Min; Tang, Yijie; Liu, Siyuan; Tang, Zhonglin
Abstract: DNA methylation is important for the epigenetic regulation of gene expression and plays a critical role in mammalian development. However, the dynamic regulation of genome-wide DNA methylation in skeletal muscle development remains largely unknown. Here, we generated the first single-base resolution DNA methylome and transcriptome maps of porcine skeletal muscle across 27 developmental stages. The overall methylation level decreased from the embryo to the adult, which was highly correlated with the downregulated expression of DNMT1 and an increase in partially methylated domains. Notably, we identified over 40 000 developmentally differentially methylated CpGs (dDMCs) that reconstitute the developmental trajectory of skeletal muscle and associate with muscle developmental genes and transcription factors (TFs). The dDMCs were significantly under-represented in promoter regulatory regions but strongly enriched as enhancer histone markers and in chromatin-accessible regions. Integrative analysis revealed the negative regulation of both promoter and gene body methylation in genes associated with muscle contraction and insulin signaling during skeletal muscle development. Mechanistically, DNA methylation affected the expression of muscle-related genes by modulating the accessibly of upstream myogenesis TF binding, indicating the involvement of the DNA methylation/ SP1 / IGF2BP3 axis in skeletal myogenesis. Our results highlight the function and regulation of dynamic DNA methylation in skeletal muscle development.